Efficacy of classification-specific treatment and adherence on outcomes in people with chronic low back pain. A one-year follow-up, prospective, randomized, controlled clinical trial. (August 2016) - Van Dillen, Linda R.; Norton, Barbara J.; Sahrmann, Shirley A.; Evanoff, Bradley A.; Harris-Hayes, Marcie; Holtzman, Gregory W.; Earley, Jeanne; Chou, Irene; Strube, Michael J.
Abstract: Background: It is unknown if low back pain (LBP) outcomes are enhanced by classification-specific treatment based on the Movement System Impairment classification system. The moderating effect of adherence to treatment also is unknown. Objectives: Compare the efficacy of a classification-specific treatment (CS) and a non classification-specific (NCs) treatment and examine the moderating effect of adherence on outcomes. Design: 2 center, 2 parallel group, prospective, randomized, clinical trial. Method: Participants with chronic LBP were classified and randomized. Self-report data was obtained at baseline, post-treatment, and 6 and 12 months post-treatment. The primary outcome was the modified Oswestry Disability Index (mODI; 0–100%). Treatment effect modifiers were exercise adherence and performance training adherence. An intention to treat approach and hierarchical linear modeling were used. Results: 47 people received CS treatment, 54 people received NCs treatment. Treatment groups did not differ in mODI scores ( p > 0.05). For both groups, scores improved with treatment ( p < 0.05), plateaued at 6 months ( p > 0.05), and minimally regressed at 12 months ( p < 0.05). Performance training adherence had a unique, independent effect on mODI scores above and beyond the effect of exercise adherence ( p < 0.05). There were no treatment group effects on the relationship between mODI scores and the two types of adherence ( p < 0.05). Conclusions: There were no differences in function between the two treatment groups (CS and NCs). In both treatment groups, people with chronic LBP displayed clinically important long-term improvements in function. When both forms of adherence were considered, the improvements were uniquely related to adherence to performance training. Highlights: Outcomes were similar for the two treatment groups. Both treatments included exercise and performance training to modify functional activities. Both groups adhered more and longer to performance training than to exercise. Adherence to performance training had a unique and independent effect on outcomes above and beyond adherence to exercise.